Nature of Reactive Sites in TS-1 from 15N Solid-State NMR and Ti K-Edge X-Ray Absorption Spectroscopic Signatures Upon Pyridine Adsorption - Lätsch, Lukas; Kaul, Christoph J; Yakimov, Alexander V; McEntee, Rhaínna; Baerdemaeker, Trees De; Parvulescu, Andrei-Nicolae; Seidel, Karsten; Teles, J Henrique; Copéret, Christophe (Journal of the American Chemical Society, 2024)
Ti-containing zeotypes, notably titanosilicalite-1 (TS-1), are prominent examples of heterogeneous catalysts that have found applications in selective oxidation processes with hydrogen peroxide. Despite extensive characterization studies including using various probe molecules to interrogate the nature and the local environment of Ti sites, their detailed structure (as well as reactivity) remains elusive. Here, we demonstrate that using low temperature 15N magic angle spinning (MAS) ssNMR spectroscopy of adsorbed pyridine on TS-1 combined with Ti K-edge XANES on a range of samples (dehydrated, hydrated, contacted with H2O2 and pyridine) provides unique information regarding the Ti sites, highlighting their reactivity and dynamic nature. While dehydrated TS-1 shows only Lewis acid sites, the presence of H2O generates Brønsted acid sites, whose amount correlates with water loading. Moreover, the methodology─based on 15N ssNMR and Ti K-edge XANES─applied to a library of samples with various Ti-loadings and absence of extraframework TiO2 also enables quantification of the amount of Lewis acid sites and to establish a structure-activity descriptor (ratio of pyridine adsorbed on silanols vs titanium). Complementary analysis including computational modeling reveals that the reaction of Ti sites with H2O generates an acidic bridging silanol Ti-(OH)-Si, upon hydrolysis of one Ti-O-Si linkage, where Ti expands its coordination from four to pentacoordinated according to XAS.Ti-containing zeotypes, notably titanosilicalite-1 (TS-1), are prominent examples of heterogeneous catalysts that have found applications in selective oxidation processes with hydrogen peroxide. Despite extensive characterization studies including using various probe molecules to interrogate the nature and the local environment of Ti sites, their detailed structure (as well as reactivity) remains elusive. Here, we demonstrate that using low temperature 15N magic angle spinning (MAS) ssNMR spectroscopy of adsorbed pyridine on TS-1 combined with Ti K-edge XANES on a range of samples (dehydrated, hydrated, contacted with H2O2 and pyridine) provides unique information regarding the Ti sites, highlighting their reactivity and dynamic nature. While dehydrated TS-1 shows only Lewis acid sites, the presence of H2O generates Brønsted acid sites, whose amount correlates with water loading. Moreover, the methodology─based on 15N ssNMR and Ti K-edge XANES─applied to a library of samples with various Ti-loadings and absence of extraframework TiO2 also enables quantification of the amount of Lewis acid sites and to establish a structure-activity descriptor (ratio of pyridine adsorbed on silanols vs titanium). Complementary analysis including computational modeling reveals that the reaction of Ti sites with H2O generates an acidic bridging silanol Ti-(OH)-Si, upon hydrolysis of one Ti-O-Si linkage, where Ti expands its coordination from four to pentacoordinated according to XAS.